Mortality and extent of coronary artery disease in 2776 patients with type 1 diabetes undergoing coronary angiography: A nationwide study. (29th August 2020) - Ritsinger, V; Hero, C; Svensson, AM; Saleh, N; Lagerqvist, B; Eeg-Olofsson, K; Norhammar, A
Abstract: Background: In a modern perspective there is limited information on mortality by affected coronary vessels assessed by coronary angiography in patients with type 1 diabetes. The aim of the present study was to characterise distribution of coronary artery disease and impact on long-term mortality in patients with type 1 diabetes undergoing coronary angiography. Design: The design of this research was a nationwide population-based cohort study. Methods: Individuals ( n  = 2776) with type 1 diabetes undergoing coronary angiography 2001–2013 included in the Swedish National Diabetes Registry and Swedish Coronary Angiography and Angioplasty Registry were followed for mortality until 31 December 2013 (mean 7.1 years). In 79% the indication was stable or acute coronary artery disease. Coronary artery disease was categorised into normal (21%), one- (23%), two- (18%), three- (29%) and left main-vessel disease (8%). Results: Mean age was 57 years and 58% were male. Mean diabetes duration was 35 years, glycated haemoglobin was 67 mmol/mol and 44% had normal or one-vessel disease. In multivariate Cox proportional analyses hazard ratio for mortality compared with normal findings was 1.09 (95% confidence interval 0.80–1.48) for one, 1.43 (1.05–1.94) for two, 1.47 (1.10–1.96) for three and 1.90 (1.35–2.68) for left main-vessel disease. Renal failure 2.29 (1.77–2.96) and previous heart failure 1.76 (1.46–2.13) were highly associated with mortality. Standard mortality ratio the first year was 5.55 (4.65–6.56) and decreased to 2.80 (2.18–3.54) after five years. Conclusions: In patients with type 1 diabetes referred for coronary angiography mortality is influenced by numbers of affected coronary vessels. The overall mortality rate was higher compared with the general population. These results support early intensive prevention of coronary artery disease in this population.